Public expenditure and financial accountability assessing public financial management performance and influencing reform processes. - Hawke, Lewis (Governance briefs., 2017)
Public Expenditure and Financial Accountability framework is a tool to assess the status of a country public financial management system. This brief describes its evolution, the upgraded 2016 framework, and key lessons learned.